Recovery of hydrogen from hydrogen sulfide by indirect electrolysis process. (26th February 2019) - Huang, Haiyan; Shang, Jie; Yu, Ying; Chung, Keng H.
Abstract: Recovery hydrogen from hydrogen sulfide is an effective way of utilizing exhaust gas. In this paper, removal of hydrogen sulfide by indirect electrochemical process was studied using acidic aqueous solution of Fe 3+ /Fe 2+ as the electrochemical intermediate. Solid polymer electrolyte was applied to hydrogen production by indirect electrolysis of H2 S, in which the anode was graphite cloth, the cathode was the platinized graphite cloth, and the membrane was proton exchange membrane. The results of electrolysis experiments showed the relationship of current density as a function of electrolytic voltage at constant flow rate of electrolyte, temperature, and electrolyte composition. The effect of the cathode liquid velocity on current density was small. When the flow rate of anode electrolyte was greater than 200 L/hr., the current density tended to be stable. When [Fe 3+ ]>0.20 mol/L, the concentrations of Fe 2+ and Fe 3+ ions in the anode solution had no significant impact on the current density. The current density gradually increased with temperature. In the electrolytic process of hydrogen production, the Fe 2+ ions diffused from the anode to the cathode. The amount of diffusing Fe 2+ ions gradually increased with time. The effect of Fe 2+ ions diffusion from anode to cathode on hydrogen production was discussed. Highlights: The acidic aqueous solution of Fe 3+ /Fe 2+ was the electrochemical intermediate. Solid polymer electrolyte was used in the process of indirect electrolysis of H2 S. The current density was stable under suitable reaction conditions. The amount of Fe 2+ ions from the anode to the cathode increased with time.